Sistem Pemilihan Enam Menu Display pada Klinik menggunakan Pergerakan Kepala berbasis Nvidia Jetson Nano - Andika Kalvin Simarmata; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Based on the National Socio-Economic Survey (Susenas) in 2018, there were 30.38 million people with disabilities/14.2 percent of the total population in Indonesia. Persons with disabilities have difficulty operating electronic devices. On this basis, persons with disabilities need tools to operate these devices without physical contact. In addition, physical contact must also be minimized globally due to the COVID-19 pandemic which has spread throughout the world. The solution to this problem is to create a system that can operate electronic devices without making physical contact. This solution can be realized by using Facial Landmark-based head movements to select the display menu at the clinic with the application name "Smart Clinic". The clinic is the main focus because it is the most vulnerable place to the spread of COVID-19. This system works by classifying head movements to the right, left, up, and down. The output of this system is in the form of six menu options. The results obtained from the research accuracy of 90% for the distance of the user as far as 60 cm from the camera, 85% distance of the user as far as 75 cm and 82% distance of the user as far as 90 cm. The distance is selected based on the user's safe viewing distance with the monitor screen, which is in the range of 50-100 cm. This system also has a relatively fast computation time of 0.0034745 s.